The Effect of a Consumer-Based Activity Tracker Intervention on Accelerometer-Measured Sedentary Time Among Retirees: A Randomized Controlled REACT Trial - Suorsa Kristin; Leskinen Tuija; Pulakka Anna; Pentti Jaana; Löyttyniemi Eliisa; Heinonen Ilkka; Vahtera Jussi; Stenholm Sari (United States, 2022)
Background: Effective strategies to reverse the increasing trend of sedentary behavior after retirement are needed. The aim of this study was to examine the effect of 12-month activity tracker-based intervention on daily total and prolonged sedentary time (≥60 min) among recent retirees.
Methods: Randomization to intervention and control groups was performed to 231 retirees (mean age 65.2 (SD 1.1) years, 83% women). Intervention participants wore a consumer-based wrist-worn activity tracker (Polar Loop 2, Polar, Kempele, Finland), including daily activity goal, every day and night for 12 months. The activity tracker also gave vibrating reminders to break up uninterrupted inactivity periods after 55 minutes. A wrist-worn triaxial ActiGraph wGT3X-BT accelerometer was used to measure sedentary time at baseline and at 3-, 6- and 12-month time points.
Results: The use of an activity tracker did not reduce daily total or prolonged sedentary time over 12 months (p values for time*group interaction 0.27 and 0.39, respectively). In the post-hoc analysis focusing on short- and medium-term effects on prolonged sedentary time, no differences between the intervention and control groups over three months were found, but a tendency for a greater decrease in prolonged sedentary time in the intervention group over six months was seen (mean difference in changes between the groups 29 min, 95% CI -2 to 61).
Conclusions: The activity tracker with inactivity alerts did not elicit changes in sedentary time over 12 months among recent retirees. Alternative approaches may be needed to achieve long-term changes in sedentary time among retirees.